Release on Cotton Rosser and Lem Boughner at Cow Palace - News Bureau, California Polytechnic State College::::::author:::
Release to Long Beach Independent about Cotton Rosser and Lem Boughner attending the National Junior Livestock exposition at San Francisco's Cow Palace.